Water Recovery Assessment from Hypersaline Lithium-Rich Brines Using Membrane Distillation-Crystallization - Romero-Figueroa, J; Quilaqueo-Novoa, M (ELSEVIER, 2022)
The current lithium extraction from hypersaline salt-lake brines is causing concerns, mainly due to the evapo-ration and loss of around 90 % of the water contained in the brines, tensioning the relationship between com-munities and industrial companies located in zones with a severe water scarcity. This study assesses the water recovery from synthetic hypersaline brines -mimicking the contents variability of Na, K, and Mg -using a Membrane Distillation-Crystallization process. An evaluation of the operational parameters of the process, such as feed temperature, flowrate and water activity was carried-out using a Response Surface Methodology. Final validation was performed to assess the process performance by comparing a real brine from Maricunga salt-lake (Chile) and a synthetic brine. An average flux of around 3.5 kg/m2 h at 60 degrees C brine feed temperature was ob-tained for real and synthetic brines, achieving a high quality recovered freshwater (electrical conductivity <40 mu S/cm) and low contents of ions.